Trends in Nosocomial Bloodstream Infections following Health Care Restructuring in Alberta between 1999 and 2005. Issue 1 (2010) - Lee, Mao-Cheng; Saxinger, Lynora; Forgie, Sarah E; Taylor, Geoffrey
Abstract : OBJECTIVE: A previous study at the University of Alberta Hospital/Stollery Children's Hospital in Edmonton, Alberta, revealed an increase in hospital-acquired bloodstream infection (BSI) rates associated with an increase in patient acuity during a period of public health care delivery restructuring between 1993 and 1996. The present study assessed trends in BSIs since the end of the restructuring. DESIGN: Prospective surveillance for BSIs was performed using Centers for Disease Control and Prevention (USA) criteria for infection. BSI cases between January 1, 1999, and December 31, 2005, were reviewed. Available measures of patient volumes, acuity and BSI risk factors between 1999 and 2005 were also reviewed from hospital records. SETTING: The University of Alberta Hospital/Stollery Children's Hospital (617 adult and 139 pediatric beds, respectively). PATIENTS: All pediatric and adult patients admitted during the above-specified period with one or more episodes of BSIs. RESULTS: There was a significant overall decline in the BSI number and rate over the study period between 1999 and 2005. The downward trend was widespread, involving both adult and pediatric populations, as well as primary and secondary BSIs. During this period, the number of hospital-wide and intensive care unit admissions, intensive care unit central venous catheter-days, total parenteral nutrition days and number of solid-organ transplants were either unchanged or increased. Gram-positive bacterial causes of BSIs showed significant downward trends, but Gram-negative bacterial and fungal etiologies were unchanged. CONCLUSIONS: These data imply that, over time, hospitals can gradually adjust to changing patient care circumstances and, in this example, control infectious complications of health care delivery.